Superluminal graviton condensate vacuum - Markoulakis, Emmanouil N. (International Journal of Physical Research, 2024)
In this study, we argue fundamentally and physically on the nature of the graviton as the only elementary particle in the universe, constituting the fabric of vacuum spacetime and all matter and all energy forms. We demonstrate that the universe's functioning is consistent with the current laws of physics and that a non-tachyonic graviton string-particle carrying superluminal energy exists. The graviton model proposed herein unifies dark energy, quantum gravity, and dressed zero-point vacuum energy field in a single energy manifold. The model provides an alternative interpretation of the vacuum energy, the dark energy, and the cosmological constant value as well as an explanation for the cosmological “coincidence problem”. Our model describes the zero-point vacuum energy as an evaporation product of hidden compacted extra dimensions superluminal energy of the universe, rather than being due to any supersymmetry fine-tuned fields cancellation. Furthermore, the proposed model also predicts how the graviton's superluminal oscillation is ticking down the remaining lifetime of the universe, acting as a cosmological clock. Spacetime should end after a Big Freeze or a Big Rip scenario governed by a global vacuum instantaneous catastrophic event, to which a new cycle of Big Bang follows. Our model explains why the massless spin 2 in-place superluminal vibrating graviton and condensate consisting everything including spacetime must be essentially the only massless cold boson elementary particle and why fundamentally the vacuum is superluminal condensate energy. An experiment with the Atlas detector is proposed to indirectly verify the theory by measuring potential superluminal propagation of dark photons. Essentially, the research reveals that the entire dark sector consists of superluminal energy, making it directly undetectable. Additionally, it suggests that quantum gravity originates from the dark sector.